Huerto pedagógico comunitario: un aporte para el fortalecimiento de la educación ambiental en la institución Educativa la Buitrera, Cali - Colombia (2020)
The present work is a contribution to the strengthening of environmental education, in which a transversal strategy is proposed in and out of class through school gardens, this allows teaching to be more empirical and students of the La Buitrera Educational Institution to appropriate and learn to grow their own products. All this in order to develop skills to strengthen the link with nature and in turn these spaces allow them to acquire knowledge and understand environmental issues for the adaptation of spaces where the school garden can be implemented as a project of enterprise that favours the educational institution and the Buitrera community, contributing to food security in this rural area of Cali. This process consisted of three steps, the first one was to realize a characterization of the state of the five headquarters of the Educational Institution Buitrera in terms of spaces for the adaptation of the orchards in which we find ideal spaces and with a strategic location for the attachment and appropriation of the students with the project. The second step was the design of the orchards in each of the five headquarters of the institution, these designs were made listening to proposals from students and teachers about what they would like to plant, this without detracting from the emphasis of aromatic/ medicinal plants for the Hierbaprolim project. Finally, the third step was to promote transversal strategies within and outside the classroom with the teachers, with this we promote a sense of belonging not only of students but also of teachers in which the classes are articulated with topics related to the school garden. At the end of this work we could see a noticeable change in the commitment and good attitude of the educational community with the school gardens in all the headquarters of the institution, it was pleasing to see how the teachers and students joined together to try to articulate the class themes with the vegetable garden, all in order to welcome the vegetable garden also as an entrepreneurship opportunity